Implementasi Metode Chroma Key Pada Animasi 3D Prosedur Penyelamatan Diri Dari Kapal Tenggelam - Siti Sundari; Mardiana Mardiana; Eko Prabowo (Program Studi Sistem Informasi, 2019)
Three dimensional animation is one of the technologies that developed nowadays. Using three-dimensional animation, we can describe something we want to convey to others and the wider community. Green screen is a special effect used to combine two images. This technique is also known as Chroma Key, color-keying, Color Separation Overlay (CSO) or blue screen. Chroma Key or blue screen / green screen, also called color keying, color separation overlay is a technique used in film and television, to change the background color with another background image using the Chroma Key technique, background of objects recorded with a video camera can be replaced with other desired backgrounds. Here the author uses 3D Animation to change the background of green screen because it is interesting and will be easily remembered by the public.Keywords: 3D animation, Green screen, Chroma Key